Answer:
y = -3x + 5
Step-by-step explanation:
Since the line is parallel, we know that the slope of our line must be equal to the one given.
The given equation is:
y = -3x + 4
and thus, it has a slope of -3
As such, our unknown equation...
y = kx + m
...must have the same k-value, or the same slope, of -3.
y = -3x + m
Now we just need to find m. We know that our line passes through the point (2, -1), or in other words, when x = 2, y = -1
We can put these values for x and y into our equation.
y = -3x + m
-1 = -3 * 2 + m
-1 = -6 + m
Adding 6 to both sides:
5 = m
m = 5
Putting m = 5 into our equation:
y = -3x + m
y = -3x + 5
..we find that our equation is
y = -3x + 5